ANALISA PENGARUH PROMOSI ONLINE TERHADAP CITRA MEREK DAN DAMPAKNYA PADA PERSPEKTIF PELANGGAN PT CATUR MITRA SEJATI SENTOSA MITRA 10 BATAM - Yulianus Hulu; Yossi Hendriati (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study aims to determine the effect of online promotion analysis on brand image and its impact on the customer perspective of PT. ccatur Mitra Sejati Sentosa Mitra 10 Batam, the type of research used is descriptive verification and the presentation of the variables studied and concluded that the object of research that becomes the independent variable is online promotion (X), brand image (Y), and customer perspective (Z). as the dependent variable. Population In this study the author used in taking probability sampling samples was the approach method used for surveys with the aim of generalization, namely the technique of determining the sample based on chance by using the Slovin formula so that the sample in this study was 99 people. The results of this study indicate the effect of online promotion analysis on brand image and its impact on the customer perspective of PT. chess true partner sentosa partner 10 batam. R Square 23,2% from these results it can be concluded that online promotion variables (X), brand image (Y), customer perspective (Z) while 76,8% influenced other variables were not examined in this study